Oikonomia theou dan oikonomia institusional: Participatio in mysterion sebagai paradigma manajemen pendidikan Kristiani Indonesia - Pontus Sitorus (KURIOS, 2025)
This article develops a theological framework for understanding Christian education management through the concept of oikonomia in Pauline and patristic theology. By analyzing the intrinsic relationship between oikonomia theou (divine management) and mysterion (the revealed plan of salvation), this article argues that the management of Christian educational institutions must be understood as participatio, the ontological and practical participation in God's work of salvation. Through exegetical analysis of key texts from Ephesians and Colossians, and by appropriating the concept of participatio from the Thomistic tradition and contemporary sacramental theology, this article offers a theological reconstitution of managerial practices that transcend the technocratic-instrumental approach. The implications of this paradigm are elaborated in the specific context of Indonesian Christian education, considering the challenges of contextualization and the need for theological-practical integration.   Abstrak Artikel ini mengembangkan suatu kerangka teologis, untuk memahami manajemen pendidikan Kristiani melalui konsep oikonomia dalam teologi Paulus dan patristik. Dengan menganalisis hubungan intrinsik antara oikonomia theou (pengelolaan ilahi) dan mysterion (rencana keselamatan yang terungkap), artikel ini berargumen bahwa manajemen institusi pendidikan Kristiani harus dipahami sebagai participation, partisipasi ontologis dan praktis dalam karya penyelamatan Allah. Melalui analisis eksegesis terhadap teks-teks kunci Efesus dan Kolose, serta apropriasi konsep participatio dari tradisi Thomistik dan teologi sakramental kontemporer, artikel ini menawarkan rekonstitusi teologis atas praktik manajerial yang melampaui pendekatan teknokratis-instrumental. Implikasi paradigma ini dijabarkan dalam konteks spesifik pendidikan Kristiani Indonesia dengan mempertimbangkan tantangan kontekstualisasi dan kebutuhan akan integrasi teologis-praktis.